Magnetic particle imaging for in vivo blood flow velocity measurements in mice. (16th March 2018) - Kaul, Michael G; Salamon, Johannes; Knopp, Tobias; Ittrich, Harald; Adam, Gerhard; Weller, Horst; Jung, Caroline
Abstract: Magnetic particle imaging (MPI) is a new imaging technology. It is a potential candidate to be used for angiographic purposes, to study perfusion and cell migration. The aim of this work was to measure velocities of the flowing blood in the inferior vena cava of mice, using MPI, and to evaluate it in comparison with magnetic resonance imaging (MRI). A phantom mimicking the flow within the inferior vena cava with velocities of up to 21 cm s −1 was used for the evaluation of the applied analysis techniques. Time–density and distance–density analyses for bolus tracking were performed to calculate flow velocities. These findings were compared with the calibrated velocities set by a flow pump, and it can be concluded that velocities of up to 21 cm s −1 can be measured by MPI. A time–density analysis using an arrival time estimation algorithm showed the best agreement with the preset velocities. In vivo measurements were performed in healthy FVB mice ( n   =  10). MRI experiments were performed using phase contrast (PC) for velocity mapping. For MPI measurements, a standardized injection of a superparamagnetic iron oxide tracer was applied. In vivo MPI data were evaluated by a time–density analysis and compared to PC MRI. A Bland–Altman analysis revealed good agreement between the in vivo velocities acquired by MRI of 4.0  ±  1.5 cm s −1 and those measured by MPI of 4.8  ±  1.1 cm s −1 . Magnetic particle imaging is a new tool with which to measure and quantify flow velocities. It is fast, radiation-free, and produces 3D images. It therefore offers the potential for vascular imaging.